The transformative role of artificial intelligence in modern dentistry - Azarenkov, Volodymyr Illich; Pereshyvailova, Iryna; Dіudina, Iryna; Zabolotnyi, Oleksandr (Perfect Publishing, 2024)
Artificial Intelligence is playing an increasingly important role in the field of dentistry, offering new opportunities to improve diagnosis, optimize treatment planning, and enhance procedure execution. Artificial Intelligence also improves methods for manufacturing prosthetic devices, thereby enhancing the quality of patient care and treatment outcomes.
Keywords: artificial intelligence; neural networks; innovative materials and medications; machine learning technologies; personalized medicine